ALD derived Fe3+- doping toward high performance P2–Na0.75Ni0.2Co0.2Mn0.6O2 cathode material for sodium ion batteries. (December 2019) - Hou, Ya'nan; Li, Xifei; Liu, Wen; Kou, Huari; Maleki Kheimeh Sari, Hirbod; Song, Xiaosheng; Li, Jianwei; Dou, Shuming; Liu, Xiaojing; Deng, Sixu; Li, Dejun; Sun, Xueliang
Abstract: The structural instability and sluggish kinetic process of the pristine Na0.75 Ni0.2 Co0.2 Mn0.6 O2 (NCM) occurring at a high working voltage result in obvious capacity loss. In this study, Fe 3+ doping onto the surface of the P2-type Na0.75 Ni0.2 Co0.2 Mn0.6 O2 (NCM) was fulfilled via post-annealing atomic layer deposition (ALD) derived Fe2 O3 layer. It indicates that the modified NCM cathode materials exhibit better crystal structure stability and electrochemical behavior than the pristine NCM at wide voltage windows of 2.4–4.5 V and 2.4–4.7 V vs. Na/Na + . Furthermore, the ALD-30C-annealing material shows a higher initial capacity of 107 mA h g −1 at 0.1C (20 mA g −1 ), and it can reach a reversible capacity of 78 mA h g −1 and Coulombic efficiency of 96.6% after 100 cycles at the cutoff voltage of 4.5 V. Amazingly, combined with reduced graphene oxide (rGO) as an anode material, the ALD-30C-annealing cathode material exhibits notable full cell performance with the specific energy density of 160 Wh kg −1 at the high voltage widows of 2.4–4.5 V after 100 cycles. The designed strategy in this work may be one of the most promising perspectives toward the high performance cathode materials for SIBs. Graphical abstract: The modified NCM with post-annealing ALD deprived Fe2 O3 exhibits superior cycling stability and rate capacity within the high working voltage of 2.4–4.5 V and 2.4–4.7 V due to the improvement of the crystal structure stability, electronic conductivity, electrochemical activity and reaction kinetics. Image 1 Highlights: The P2-type Na0.75 Ni0.2 Co0.2 Mn0.6 O2 (NCM) is successfully synthesized via sol-gel method. Post-annealing ALD deprived Fe2 O3 with various cycles significantly modifies the structure stability and electrochemical performance of the NCM. The desired electrode delivers superior cycling stability and rate capacity within the high working voltage. The full cell rGO//ALD-30C-annealing is carried out at the high voltage window of 2.4–4.5 V.